Transformasi Sistem dan Strategi Pengembangan PTKI Berbasis Multikultural: Sebuah Analisis Komparatif - Muhammad Arif Luthfi, Alfauzan Amin, Zubaedi, Hery Noer Aly, Destriani (Institut Kariman Wirayudha Sumenep, 2025)
This study investigates how Islamic Higher Education Institutions (PTKI) reinterpret state-promoted religious moderation by shifting from a tolerance-based approach to an intersubjective coherence framework that emphasizes dialogical engagement and ethical responsiveness to diversity. Using a qualitative, policy-oriented design, the research analyzes national regulations, institutional blueprints, curriculum documents, and internal quality assurance reports, complemented by relevant scholarship on multiculturalism and higher-education transformation. The analysis employs inductive coding to identify institutional patterns in framing, operationalizing, and negotiating multicultural commitments. The results show three central tendencies: national policy provides strong normative direction but limited operational clarity; PTKI demonstrate uneven levels of institutional transformation, with some embedding moderation in curriculum governance and community programs while others reduce it to symbolic compliance; and the absence of sustained intersubjective mechanisms restricts the translation of policy principles into academic culture and institutional practices. The study concludes that meaningful transformation requires strengthening dialogical accountability, redesigning curriculum integration strategies, and aligning institutional capacities with national expectations. It proposes intersubjective coherence as a practical conceptual pathway that enables PTKI to address the complexity of plural societies while maintaining academic integrity, ensuring that multicultural commitments become embedded rather than merely declared.